2017
DOI: 10.15390/eb.2016.4601
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Teaching and Learning Conceptions and Scientific Epistemological Beliefs of Pre-service Teachers’: A Longitudinal Study

Abstract: Eğitim alanındaki hızlı değişimleri sisteme yansıtmadaki kilit rolü nedeniyle öğretmenlerin yerleşik inançları ve bu inançları etkileyen değişkenler, son yıllarda araştırmacıların ilgisini çekmektedir. Araştırmalar, öğretmenlerin öğretme-öğrenme sürecinde aldıkları kararların yanı sıra sınıfta uyguladıkları etkinliklerin de büyük ölçüde, önceden var olan inançları çerçevesinde şekillendiğini göstermektedir. Bu araştırma, öğretmen adaylarının eğitimleri boyunca öğretme-öğrenme anlayışları (ÖÖA) ve bilimsel epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Bas (2014) argued that teachers' teaching-learning conceptions differed significantly by gender, professional seniority, and educational status. In addition, epistemological beliefs were also found effective in predicting teaching-learning conceptions (Akyildiz, 2014;Aypay, 2011;Bikmaz, 2017;Karhan, 2007). These findings in the literature showed that variables affecting the teaching-learning conception were general self-efficacy, individual innovativeness, seniority and gender, and epistemological beliefs.…”
Section: Teaching-learning Conceptionsmentioning
confidence: 99%
“…Bas (2014) argued that teachers' teaching-learning conceptions differed significantly by gender, professional seniority, and educational status. In addition, epistemological beliefs were also found effective in predicting teaching-learning conceptions (Akyildiz, 2014;Aypay, 2011;Bikmaz, 2017;Karhan, 2007). These findings in the literature showed that variables affecting the teaching-learning conception were general self-efficacy, individual innovativeness, seniority and gender, and epistemological beliefs.…”
Section: Teaching-learning Conceptionsmentioning
confidence: 99%
“…In the relevant literature, although there are studies (Liakopoulou, 2011;Suciu and Mata, 2011;Bas and Beyhan, 2013;Bas, 2015;Engin and Dasdemir, 2015;Bas and Senturk, 2017;Bikmaz, 2017;Senturk and Bas, 2018;Yildizli, Saban and Bastug, 2017) in which teachers' teachinglearning conceptions and perceptions of pedagogical competency are analyzed in terms of individual and different variables, (control ideologies, education beliefs, self-efficacy, scientific epistemological beliefs, lifelong learning, teaching motivation, etc.) limited studies in which the relationship between these two phenomena was examined appear.…”
Section: The Aim and Significance Of The Studymentioning
confidence: 99%
“…The epistemological beliefs and creative behaviours that teachers have will help students to find solutions to problems, solve complex relationships between variables, and develop their abilities to explain their results. In the national and international literature, studies in which epistemological beliefs are examined (Aypay, 2011;Şahin Taşkın, 2012) and the relationship with various variables are analysed (Önen Öztürk, 2016;Aslan, 2017;Ekinci, & Tican, 2017;Bıkmaz, 2017;Kutluca, Soysal, & Radmard, 2018) stand out. Studies for determining the level of creativity mostly related to creative behaviors (Özel, & Bayındır, 2015;İnel Ekici, 2016;Gökden Kaya, 2018;Batdal Karaduman & Çiftci, 2018), revealing the relationship with various variables (Yenilmez, & Yolcu, 2007;Gök, & Erdoğan, 2011;İşleyen, & Küçük, 2013;Topoğlu, 2015;Akcanca, & Cerrah Özsevgeç, 2016;Yıldız, & Baltacı, 2018;Ulusoy Yılmaz, & Yıldız, 2019), for the development of creativity (Birişçi, & Karal, 2011;Dere, 2017) attract attention.…”
Section: Introductionmentioning
confidence: 99%